2016
DOI: 10.1002/anie.201607040
|View full text |Cite
|
Sign up to set email alerts
|

Water Entrapped inside Fullerene Cages: A Potential Probe for Evaluation of Bond Polarization

Abstract: The concept of the bond polarization is a useful tool to understand chemical reactions and fundamental properties of compounds. However, experimental considerations are limited owing to its difficulty of reliable description. We demonstrated that geometrically isolated H O inside the cage of fullerene C is a possible probe to evaluate the polarization degree of covalent bonds C(C )-X (X=heteroatom) on the C cage. The H NMR relaxation times of entrapped H O have been systematically measured at variable temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…13 For H 2 @RC 59 N, the N atom embedded in the carbon-cage has influence on the magnetic relaxation of entrapped H 2 via dipole−dipole interaction, resulting in the more rapid 1 H NMR relaxation below 280 K. 13 More recently, we reported that the rotational motion of entrapped H 2 O is disturbed by electrostatic perturbation when polarized C(C 60 )−X bonds are introduced on the external sphere of C 60 . 20 The 1 H NMR Of our particular interest is the study on dynamic behavior of entrapped molecules and specific interaction with the carbon cage because it provides a precious opportunity to investigate the nature of internal sphere of fullerene cages. Here, we discussed dynamic behavior and orientations of entrapped H 2 O inside fullerene cages possessing an electron spin.…”
mentioning
confidence: 62%
“…13 For H 2 @RC 59 N, the N atom embedded in the carbon-cage has influence on the magnetic relaxation of entrapped H 2 via dipole−dipole interaction, resulting in the more rapid 1 H NMR relaxation below 280 K. 13 More recently, we reported that the rotational motion of entrapped H 2 O is disturbed by electrostatic perturbation when polarized C(C 60 )−X bonds are introduced on the external sphere of C 60 . 20 The 1 H NMR Of our particular interest is the study on dynamic behavior of entrapped molecules and specific interaction with the carbon cage because it provides a precious opportunity to investigate the nature of internal sphere of fullerene cages. Here, we discussed dynamic behavior and orientations of entrapped H 2 O inside fullerene cages possessing an electron spin.…”
mentioning
confidence: 62%
“…[22] Despite this reduced polarity, several intriguing applications of endohedral water complexes with C 60 (and its derivatives) have already been proposed. For example, it has been shown [23] that the entrapped H 2 O molecule can serve as a probe to estimate the degree of C(C 60 )-X bond polarization (X is a heteroatom attached to C 60 ) through the evaluation of 1 H NMR relaxation times in respective H 2 O@C 60 X complexes. Moreover, being geometrically confined in an open-cage C 60 , the H 2 O guest can respond to the presence of other fragments, opening up the prospect of evaluating the energetics of weak interactions (e. g. the H 2 O⋅⋅⋅(C=C) interaction [24] ) at a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that the rotation of the encapsulated water can be electrostatically perturbed by introducing polarized C(C 60 )–X (X: heteroatom) bonds. 42 …”
Section: Introductionmentioning
confidence: 99%